Comparing the effects of two different progesterone vaginal gels, Progeson™ and Crinone™, from pharmacokinetics study to clinical applications in patients undergone fresh embryo transfer and frozen-thawed embryo transfer via natural cycle endometrial preparation protocol - Yu, Cheng-Wei; Li, Wei-Jiun; Hsieh, Wen-Chi; Chen, Li-Shan; Li, Yi-Ping (Taiwanese journal of obstetrics & gynecology, 2023)
AbstractObjectiveThe pharmacokinetics performance and clinical pregnancy rate of two vaginal progesterone gel, Progeson™ and Crinone™, were compared in this study. Materials and methodsIn the pharmacokinetics performance, Progeson showed similar long-term dissolution rate as Crinone. In the clinical study, 141 subjects undergone in vitro fertilization (IVF) treatments were included to compare serum progesterone level and clinical pregnancy rates. ResultsAmong the subjects, 78 subjects received fresh embryo transfer and 63 subjects received frozen embryo transfer via natural cycle endometrial preparation protocol. In each group, subjects were given either Crinone™ or Progeson™ for luteal phase support without combination with other progesterone products. The study showed that Crinone™ group led to higher estrogen level at mid-luteal phase in the fresh embryo transfer group, and Progeson™ group led to higher progesterone level at mid-luteal phase and pregnancy test day in the frozen-thawed embryo transfer group. ConclusionSubjects received Crinone™ or Progeson™ had similar rate of pregnancy, live birth, and stillbirth in both fresh embryo transfer and frozen-thawed embryo transfer group. Thus, Progeson™ might be a suitable substitute for Crinone™ in assisted reproductive therapy.